Experimental study and Numerical simulation of stress concentration in deep drawing process without blank holder - Ayman Abd-Eltwab; almoataz Gomaa; Eman Mohamed; hammad Elmetwally (JES: Journal of Engineering Sciences)
Deep drawing without blank holder is an important process for producing circular cups which used in many applications. In this process, the blank is subjected to various loads and stresses concentrations which can lead to cup failure. This research presents a theoretical and experimental study on the effects of stresses concentrations in the deep drawing without blank holder. A simulation model was constructed the Dynamic Simulation Software - DEFORM software - to study the appropriate values for the variables. Practical experiments were conducted on universal testing machine configured for the process. Aluminum blanks were used as specimens with a thickness of 3 mm and various diameters. The process is carried out by placing the blank on the die and balancing it, then moving the punch downward to complete drawing process. During process, the specimen is subjected to loads pulling it downward. To avoid this, several suggestions were made to disperse the stresses and reduce the impact of stress concentration. The experiments were conducted at a speed of 9 mm per minute. For all experiments, the forming loads was measured during process. The results showed that avoiding stress concentration in the deep drawing process without blank holder had a significant effect in reducing the forming forces, minimizing the tearing of the samples, and improving the mechanical properties of the cups. The drawing ratio reached 2.46, which is a high percentage compared to the traditional condition, also there was a convergence between the theoretical, simulated, and experimental results